Survival analysis of time‐to‐event data in respiratory health research studies. Issue 4 (1st April 2014) - Kasza, Jessica; Wraith, Darren; Lamb, Karen; Wolfe, Rory
Abstract This article provides a review of techniques for the analysis of survival data arising from respiratory health studies. Popular techniques such as the Kaplan–Meier survival plot and the Cox proportional hazards model are presented and illustrated using data from a lung cancer study. Advanced issues are also discussed, including parametric proportional hazards models, accelerated failure time models, time‐varying explanatory variables, simultaneous analysis of multiple types of outcome events and the restricted mean survival time, a novel measure of the effect of treatment.